The impact of resistance training with different rest intervals on plasma levels of inflammatory markers in sedentary men - Zaher Etemad; Hojatollah Nıkbakht; , Mohammad ALI Azarbaıjanı; Mandana Gholamı (Selcuk University, 2016)
The aim of this study was to investigate the effect of different rest intervals between two types of 8 week's resistance training with the same volume and intensity of serum levels of homocysteine and CRP In Sedentary Men. Thirty untrained subjects who voluntarily participated in this study were randomly divided into two groups: resistance training with 90 seconds rest intervalsbetween sets (n = 10), resistance training with 180 seconds rest intervalsbetween sets (n = 10) and control group (n=10). The training programs included 8 exercises, which were performed with 50% of one repetition maximum in the first session and with 85% of one repetition maximum on the last session and in 8-12 repetitions in 3 sets. Before and after 8 weeks training period blood sampling carried out. Independent and paired t-tests were used to analyze data in a meaningful level (p lt;0.05). Results showed that There is statistically significant reduction in CRP homocysteine levels after 8 weeks of resistance training with different rest intervals in the experimental group compared to the control group (p lt;0.05).In general, we can say that the difference between rest periods in resistance training can be an important factor in changes in serum levels of homocysteine and CRP are important.